Immune checkpoint inhibitor therapy associated with IgA nephropathy: a case report and literature review - Chabannes, Melchior; Lisri, Ziriab; Lang, Stéphane; Seibel, Jean; Eberst, Guillaume; Ducloux, Didier; Pursun, Céline; Durey, Marie Agnes Dragon; Alyanakia, Marie-Alexandra; Felix, Sophie; Crepin, Thomas (Frontiers in Immunology, 2024)
Immune checkpoint inhibitors (ICIs) dramatically improve the prognosis of many malignancies but at the cost of numerous side effects, which may limit their benefits. Acute kidney injury associated with immune checkpoint inhibitors most frequently are acute tubulointerstitial nephritis (ATIN), but various cases of glomerulonephritis have also been reported. Herein, we report a case of severe IgA nephropathy (IgAN) associated with ICIs and carry out a literature review. IgAN was diagnosed in a median time of 5 months (range 1–12 months) after the initiation of ICIs, with heterogeneous severity, and usually treated by corticosteroid and discontinuation of ICIs. In contrast to our case, renal outcomes in literature were often favorable, with recovery of renal function and a reduction in proteinuria on treatment. Although IgAN related to ICIs is a much rarer complication than ATIN, it may still be underdiagnosed. Careful questioning and screening for asymptomatic hematuria should be performed before using ICIs.